Porsche : The Pursuit of Excellence - Reynolds, Bill (England CLB Publishing, 1993)
This captivating look into the golden history of the legendary car features profiles of champion sportscars and luxury touring automobiles and provides insight into how Porsches are made.
Includes Colored Illustrations
Keywords: Porsche automobiles